Rural poverty and urban proximity in Sabah, Malaysia / Jeron Joseph - Jeron , Joseph (2020)
One of the United Nations Sustainable Development Goals (SDGs) is to eradicate extreme poverty globally by 2030 in all countries including Malaysia. While Malaysia is close to achieving this target, poverty still persists in the state of Sabah. Therefore, this study examines the determinants of household poverty in rural Sabah with a focus on urban proximity. A purposefully designed survey instrument was used to gather primary data on a total of 407 rural households in 78 villages, spread across 16 poorest districts of Sabah. In addition, Geographic Information System (GIS) data on sample households and villages was collected to construct an index of urban proximity – travel time to the nearest town centre or “industrial core”. The empirical analysis utilizes multiple proxy measures of poverty such as human capital deprivation and lack of productive assets as outcome variables. For all of these measures, multivariate econometric models of household poverty model are estimated using ordinary least-squares regression method to determine the correlates of poverty. Consistent with the core-periphery model of Krugman (1991), we found that rural households with shorter commuting distance to urban centres have lower level of poverty in terms of human capital and asset ownership. This would indicate the level of poverty in terms of physical asset would depend on the proximity level of urban areas and rural households. This finding is robust to control for a host of demographic correlates of poverty and the presence of natural resources in the village, the choice of specific dimensions of poverty studied and the use of an aggregate index of household poverty (constructed using principal component analysis). Qualitative data obtained through in-depth face-to-face interviews with 10 village representatives and 15 poor households also confirms the importance of proximity to urban centres for household poverty. Respondents highlighted a variety of ways in which communication infrastructure and geographic location interact to influence travel time to urban and in turn affect their livelihood choices and household well-being. Lastly, econometric analysis of the determinants of urban proximity at the village level indicates that the distance to urban centres is primarily determined by policy variables (e.g. road infrastructure) and natural geographic barriers (e.g. presence of a river). These findings together highlight that investment in public infrastructure in rural areas can generate significant welfare gains by improving living standard and reducing spatial poverty in East Malaysia.